Membangun Kecerdasan Emosional Melalui Zikir Dalam Perspektif Al-Qur’an - Ahmad Zain Sarnoto; Susilo Wibowo (Universitas Cokroaminoto Yogyakarta, 2021)
This research is to find out how to build emotional intelligence through dhikr (remembrance of Allah) from the perspective of the Qur'an. The method used in this research is a qualitative research method with a literature study approach. Emotional intelligence is one of the most important intelligences that every individual has. Because various events experienced by humans cannot be separated from emotional involvement. This paper describes that dhikr is a spiritual behavior that is effective in building emotional intelligence in terms of various interpretations of the verses of the Al-Qur'an, Islamic spiritual studies (Sufism), and exploration of the potential for human self and psyche. Indicators of emotional intelligence through dhikr in various verses of the Qur'an: (1) the heart becomes calm in Surat ar Ra'du verse 28; (2) the heart is opened by the light of Allah in Surat Al-Zumar verse 22; (3) gratitude for the blessings given by Allah in Surah Al-Maidah verse 11; (4) introsection of one's own potentials and weaknesses in Surah Maryam verse 67; (5) building emotional intelligence in Surat Al-Hijr verses 97-98; and various other verses.